The situated politics of belonging - Yuval-Davis, Nira; Kannabirān, Kalpana; Vieten, Ulrike (Sage studies in international sociology, 2006)
This collection of essays examines the racialized and gendered effects of contemporary politics of belonging, issues which lie at the heart of contemporary political and social lives. It encompasses critical questions of identity and citizenship, inclusion and exclusion, emotional attachments, violent conflicts and local/global relationships. The range - geographically, thematically and theoretically - covered by the chapters reflects current concerns in the world today. A timely contribution to the ongoing debates in the field, it will be a valuable companion to scholars working in the areas.